The Association of ghrelin and leptin in policystic ovarian syndrome - Nurul Jannah Ismail
The hormone ghrelin has been extensively studied since its discovery in 1999. It is mainly secreted by stomach cells and found in other tissues, such as the hypothalamus, pituitary, pancreas, lung tissue, placenta, and ovaries. Another hormone, leptin, discovered in 1994, is produced by white adipose tissue that sends information to the brain regarding the amount of fat stored in the body. It is also known as the satiety hormone that gives negative energy balance in humans and involves a long list of endocrine functions, including obesity, insulin resistance, hyperandrogenism, and polycystic ovary syndrome (PCOS). Although PCOS is one of the common endocrinopathies that we know affecting women of reproductive age, to date, there are no clear etiology and pathophysiology for it. The term “polycystic ovary syndrome” comprises more than its simple name. It encompasses a broader spectrum of signs and symptoms of ovarian dysfunction. It also forms a heavy socioeconomic burden to the country besides psychological impact. Hence, it is critical to clarify the etiology of PCOS to decrease the burden of this disease. It is disheartening that there is no complete cure for PCOS, and the exact etiology of PCOS has not been fully understood. Although several studies were published concerning the link between ghrelin and leptin with PCOS, the inconsistent findings render the relationship controversial. Thus, in this review, we discussed the connection between PCOS and the hormones and tried to understand their connection. We also highlighted the gaps in previous studies. Current knowledge shows that ghrelin and leptin could have a possible link to PCOS. Further understanding of this relationship may lead to a better understanding of the etiology of PCOS, advancement of its management, and discovery of future pharmacological intervention.